Method for manufacturing self-supporting film for negative electrode of lithium secondary battery and self-supporting film for negative electrode of lithium secondary battery manufactured by method
By using ternary block copolymers containing soft blocks and hard blocks as binders in the negative electrode manufacturing of lithium secondary batteries, the high manufacturing cost of negative electrodes, poor mechanical and physical properties and electrochemical stability in the prior art are solved. The problem of insufficient properties has achieved a negative electrode self-supporting film with high tensile strength and electrochemical stability.
Patent Information
- Application Number
- CN202311659450.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-08-14
- Filing Date
- 2023-12-06
- Publication Date
- 2025-02-21
AI Technical Summary
The negative electrode manufacturing technology of existing lithium secondary batteries has shortcomings in terms of cost, mechanical physical properties and electrochemical stability, especially in the development of solvent-free dry manufacturing technology.
A ternary block copolymer containing soft blocks and hard blocks is used as a binder to form a self-supporting film for the negative electrode of the lithium secondary battery through a dry film making process. The adhesive consists of soft blocks (derived from aliphatic or cycloaliphatic diene monomers) and hard blocks (derived from ethylenically unsaturated monomers containing aromatic rings), with excellent mechanical and physical properties and Electrochemical stability.
The high tensile strength, electrochemical stability and cost-effectiveness of the negative electrode of the lithium secondary battery are achieved, and a stable three-dimensional network structure is established by forming a strong interaction with the combination of the negative electrode active material and conductive material.
Smart Images

Figure CN119495713A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a method for manufacturing a self-supporting film for a negative electrode of a lithium secondary battery using a binder containing a ternary block copolymer containing a soft block and a hard block, and a self-supporting film for a negative electrode of a lithium secondary battery manufactured by the method. Background Art
[0002] Since its first commercialization in the 1990s, lithium secondary batteries have been widely used in the portable electronic device market and continue to attract attention as the most studied energy storage system. Due to the characteristics of lithium secondary batteries such as high driving voltage, high energy density, low self-discharge rate, high rate performance and long cycle stability, lithium secondary batteries have the elements suitable as energy sources for electric vehicles.
[0003] However, lithium secondary batteries used in electric vehicles face three major problems: safety, operating time, and cost. The safety and operating time issues can be solved by all-solid-state batteries, but cost is a factor that hinders the widespread application of lithium secondary batteries, so a lot of research is being conducted to reduce the cost of lithium secondary batteries.
[0004] Reducing the energy consumption required for manufacturing or increasing the thickness of the electrode is one of the most effective ways to reduce the manufacturing cost of lithium secondary batteries. The existing electrode manufacturing technology is to form an electrode by casting a slurry mixed with an electrode active material, a polymer binder and a conductive additive in water or an organic solvent on a current collector and drying and pressing it. The energy required to prepare the slurry and coat it on the current collector as described above accounts for about 50% of the energy consumption of the entire manufacturing process. Therefore, in order to reduce the manufacturing cost of lithium secondary batteries, a process for manufacturing electrodes by a solvent-free dry method has been studied.
[0005] Although a lot of research has been done on dry electrode manufacturing technology, the development of dry negative electrode manufacturing technology for manufacturing negative electrodes with good formability and mechanical physical properties such as electrochemical stability and tensile strength is still insufficient, so research and development are needed. Summary of the invention Technical issues to be solved
[0006] The present invention aims to solve the above-mentioned problems. The purpose of the present invention is to provide a self-supporting film for the negative electrode of a lithium secondary battery and a method for manufacturing the same, a negative electrode for a lithium secondary battery including the self-supporting film for the negative electrode, and a lithium secondary battery. In the self-supporting film for the negative electrode of the lithium secondary battery, an adhesive comprising a ternary block copolymer containing a hard block that contributes to excellent mechanical and physical properties and a soft block with flexibility is used. Therefore, the self-supporting film is easy to shape and is stable even at negative potentials. It can be firmly bonded to the negative electrode active material, and has excellent tensile strength to form a three-dimensional network, so that it can be firmly bonded to the negative electrode active material and the conductive material. Technical Solution
[0007] According to one embodiment of the present invention, there is provided a method for manufacturing a self-supporting film for a negative electrode of a lithium secondary battery, the method comprising the step of forming a negative electrode active material layer by a film-making process using a negative electrode-forming composition for a lithium secondary battery comprising a negative electrode active material, a conductive material and a binder, wherein the binder comprises a ternary block copolymer, the ternary block copolymer comprising: a soft block, the soft block is derived from an aliphatic or alicyclic diene monomer, and is in a rubber phase at room temperature; and a first hard block and a second hard block, the first hard block and the second hard block are respectively connected to the two ends of the soft block, the first hard block and the second hard block are derived from an ethylenically unsaturated monomer containing an aromatic ring, and are in a glass phase at room temperature, and the binder comprises an average diameter (D 50 ) are particles of 1 μm or more and 50 μm or less.
[0008] In addition, according to another embodiment of the present invention, a self-supporting film for a negative electrode of a lithium secondary battery is provided, wherein the self-supporting film for a negative electrode of a lithium secondary battery comprises a negative electrode active material layer, wherein the negative electrode active material layer comprises a plurality of domains of negative electrode active materials, a plurality of domains of conductive materials and a binder, wherein the binder comprises a ternary block copolymer, wherein the ternary block copolymer comprises: a soft block, wherein the soft block is derived from an aliphatic or alicyclic diene monomer and is in a rubber phase at room temperature; and a first hard block and a second hard block, wherein the first hard block and the second hard block are respectively connected to the two ends of the soft block, wherein the first hard block and the second hard block are derived from an ethylenically unsaturated monomer containing an aromatic ring and are in a glass phase at room temperature, and wherein the binder has a discontinuous columnar morphology connecting any one domain of active material or domain of conductive material with another domain of active material or domain of conductive material.
[0009] According to another embodiment of the present invention, there is provided a negative electrode for a lithium secondary battery, the negative electrode for a lithium secondary battery comprising: a current collector; and a self-supporting film for the negative electrode of the lithium secondary battery disposed on the current collector.
[0010] According to one embodiment of the present invention, there is provided a lithium secondary battery, the lithium secondary battery comprising: a negative electrode for the lithium secondary battery; a positive electrode for the lithium secondary battery; and an electrolyte. Beneficial Effects
[0011] By using the method of manufacturing a self-supporting film for a negative electrode of a lithium secondary battery of the present invention, a self-supporting film for a negative electrode of a lithium secondary battery and a negative electrode for a lithium secondary battery and a lithium secondary battery using the self-supporting film for a negative electrode can be manufactured. The binder in the self-supporting film for a negative electrode of a lithium secondary battery is bonded to the negative electrode active material or the conductive material through a strong interaction, so that it has electrochemical stability even at a negative potential, and has excellent tensile strength and is easy to form. BRIEF DESCRIPTION OF THE DRAWINGS
[0012] Figure 1 : is a diagram schematically showing the internal structure of a binder included in a self-supporting film for a negative electrode of a lithium secondary battery according to one embodiment of the present invention.
[0013] Figure 2a is a diagram schematically showing a method of manufacturing a self-supporting film for a negative electrode of a lithium secondary battery according to one embodiment of the present invention.
[0014] Figure 2b : is a diagram schematically showing a change mechanism of a binder in a process of manufacturing a self-supporting film for a negative electrode of a lithium secondary battery according to one embodiment of the present invention.
[0015] Figure 3a to Figure 3c : is a diagram showing a SEM image of the self-supporting film for a negative electrode of a lithium secondary battery according to Example 1.
[0016] Figure 3d 1 is a diagram showing a network structure formed by a binder and a negative electrode active material in a negative electrode self-supporting film for a lithium secondary battery according to Example 1.
[0017] Figure 3e and Figure 3f These are diagrams showing SEM images of a styrene-butadiene-styrene block copolymer (SBS) and a negative electrode forming composition (mixed powder) containing SBS before producing a self-supporting film for a negative electrode of a lithium secondary battery.
[0018] Figure 3g 3 is a diagram showing a SEM image of the negative electrode self-supporting film for a lithium secondary battery according to Comparative Example 1.
[0019] Figure 3h This is a diagram showing a network structure formed by a binder and a negative electrode active material in a negative electrode self-supporting film for a lithium secondary battery according to Comparative Example 1.
[0020] Figure 3i and Figure 3j 3 is a diagram showing a SEM image of the negative electrode self-supporting film for a lithium secondary battery according to Comparative Example 2. DETAILED DESCRIPTION
[0021] Hereinafter, a method for manufacturing a self-supporting film for a negative electrode of a lithium secondary battery and a self-supporting film for a negative electrode of a lithium secondary battery manufactured by the method will be described in detail so that those skilled in the art can easily implement the invention.
[0022] As part of the scheme for reducing the manufacturing cost of lithium secondary batteries, the electrode manufacturing process of dry method has been actively studied.Representatively, there is a technology for using polytetrafluoroethylene (PTFE) to manufacture the positive electrode of lithium secondary batteries with dry method, however, because PTFE has a low minimum unoccupied molecular orbital (lowest unoccupied molecular orbitals, LUMO) level and easily accepts electrons, it is electrochemically unstable in a negative potential environment, so the negative electrode of the lithium secondary battery manufactured using PTFE as an adhesive has a problem of showing poor cycle stability. In addition, when using PTFE to manufacture negative electrode, the decomposition of PTFE adhesive occurs during initial charging, so there is also a problem of reduced initial efficiency of lithium secondary batteries.
[0023] Therefore, the present inventors studied a binder that is electrochemically stable even at a negative potential and a method for producing an electrode using the binder, and ultimately invented a technology for producing a self-supporting film for a negative electrode by a dry process as described below.
[0024] According to one embodiment of the present invention, a method for manufacturing a self-supporting film for a negative electrode of a lithium secondary battery includes the step of forming a negative electrode active material layer by a film-making process using a negative electrode-forming composition for a lithium secondary battery comprising a negative electrode active material, a conductive material and a binder, wherein the binder comprises a ternary block copolymer, the ternary block copolymer comprising: a soft block, the soft block is derived from an aliphatic or alicyclic diene monomer, and is in a rubber phase at room temperature; and a first hard block and a second hard block, the first hard block and the second hard block are respectively connected to the two ends of the soft block, the first hard block and the second hard block are derived from an ethylenically unsaturated monomer containing an aromatic ring, and are in a glass phase at room temperature, and the binder comprises a plurality of tertiary blocks having an average diameter (D 50 ) are particles of 1 μm or more and 50 μm or less.
[0025] The average diameter of the binder (D 50 ) refers to the diameter corresponding to 50% accumulation in the volume cumulative distribution measured by a laser diffraction / scattering particle size distribution measuring device.
[0026] The soft block may be in a rubber phase at room temperature as long as it includes repeating units derived from an aliphatic diene monomer and / or an alicyclic diene monomer, and specifically, may be derived from an aliphatic diene monomer including at least one selected from a butadiene monomer, a pentadiene monomer, and a hexadiene monomer.
[0027] The butadiene-based monomer may include at least one selected from the group consisting of 1,2-butadiene, 1,3-butadiene, isoprene, and chloroprene.
[0028] The pentadiene monomer may include 1,2-pentadiene, 1,3-pentadiene, 1,4-pentadiene, 2,3-pentadiene, 2-methyl-1,3-pentadiene, 2-methyl-1,4-pentadiene, 2-methyl-2,3-pentadiene, 2-methyl-2,4-pentadiene, 3-methyl-1,3-pentadiene, 3-methyl-1,4-pentadiene, 4-methyl-1,3-pentadiene, 2-ethyl-1,3-pentadiene, At least one of pentadiene, 2-ethyl-1,4-pentadiene, 2-ethyl-2,4-pentadiene, 3-ethyl-1,3-pentadiene, 3-ethyl-1,4-pentadiene, 4-ethyl-1,3-pentadiene, 1-chloro-1,3-pentadiene, 1-chloro-2,4-pentadiene, 2-chloro-1,3-pentadiene, 3-chloro-1,3-pentadiene, 3-chloro-1,4-pentadiene, and 5-chloro-1,3-pentadiene.
[0029] The hexadiene-based monomer may include 1,2-hexadiene, 1,3-hexadiene, 1,4-hexadiene, 1,5-hexadiene, 2,3-hexadiene, 2,4-hexadiene, 2,5-hexadiene, 3,5-hexadiene, 2-methyl-1,3-hexadiene, 2-methyl-1,4-hexadiene, 2-methyl-1,5-hexadiene, 2-methyl-2,3-hexadiene, 2-methyl-2,4-hexadiene, 3-methyl-1,2-hexadiene, 3-methyl-1,3-hexadiene, 3-methyl-1,4-hexadiene, 3-methyl-1,5-hexadiene, 2-methyl-2,3-hexadiene, 2-methyl-2,4-hexadiene, At least one of methyl-1,5-hexadiene, 3-methyl-2,4-hexadiene, 3-methyl-2,5-hexadiene, 4-methyl-1,3-hexadiene, 4-methyl-1,4-hexadiene, 4-methyl-2,3-hexadiene, 5-methyl-1,3-hexadiene, 5-methyl-1,4-hexadiene, 2-ethyl-1,3-hexadiene, 2-ethyl-1,4-hexadiene, 3-ethyl-1,2-hexadiene, 3-ethyl-1,3-hexadiene, 3-ethyl-1,4-hexadiene and 3-ethyl-1,5-hexadiene.
[0030] The ternary block copolymer including the soft block has the characteristics of excellent flexibility, extrusion moldability and wear resistance.
[0031] The first hard block and the second hard block only need to contain repeating units derived from an ethylenically unsaturated monomer containing an aromatic ring and be in a glass phase at room temperature. Specifically, the aromatic ring contained in the ethylenically unsaturated monomer may be a substituted or unsubstituted benzene ring or a substituted or unsubstituted naphthalene ring.
[0032] In addition, the aromatic ring may be connected to the main chain or the side chain of the repeating unit of the first hard block and the second hard block, and preferably may be connected to the side chain of the repeating unit of the first hard block and the second hard block.
[0033] The first hard block and the second hard block may each independently be derived from an aromatic ring-containing ethylenically unsaturated monomer including at least one of a styrene-based monomer and an aromatic (meth)acrylic-based monomer.
[0034] The styrene-based monomer may include at least one selected from styrene, α-methylstyrene, p-methylstyrene, p-methoxystyrene, p-ethoxystyrene, tert-butoxystyrene, p-acetoxystyrene, p-chlorostyrene, p-bromostyrene, 2,4-dimethylstyrene, 3,5-dimethylstyrene, and 2,4,6-trimethylstyrene.
[0035] The aromatic (meth)acrylic monomer may include at least one selected from the group consisting of benzyl acrylate, benzyl methacrylate, phenoxyacrylate, phenoxymethacrylate, phenyl acrylate, phenyl methacrylate, phenethyl acrylate, and phenethyl methacrylate.
[0036] The first hard block and the second hard block can be firmly combined with the negative electrode active material or the conductive material through the π-π interaction based on the aromatic ring structure contained in the repeating unit. In addition, the first hard block and the second hard block are cross-linked (connected) by physical bonds with relatively low binding energy, for example, they can maintain their shape and size at a temperature equal to or lower than the glass transition temperature, but can be easily formed at a temperature equal to or higher than the glass transition temperature. Therefore, when a self-supporting film for a negative electrode is manufactured at a temperature at which the ternary block copolymer can be formed, each hard block contained in the ternary block copolymer is flexibly deformed while being combined with the negative electrode active material or the conductive material, so that the binder portion can provide a physical cross-linking point (connection point) with a linear (intermittent columnar or linear) morphology, and a solid three-dimensional network structure can be formed with this as the center.
[0037] In addition, the first hard block and the second hard block may impart high strength characteristics to the ternary block copolymer including the first hard block and the second hard block.
[0038] Based on the total content of the ternary block copolymer, the content of the first hard block and the second hard block may be 10-60% by weight, preferably 15-55% by weight, and more preferably 20-50% by weight. When the content of the first hard block and the second hard block meets the above numerical range, the binding force can be further improved due to the strong interaction with the negative electrode active material or the conductive material, and the ternary block copolymer can have appropriate flexibility, so it can have more excellent moldability.
[0039] The weight average molecular weight of each of the first hard block and the second hard block may be 9000 g / mol or more and 20000 g / mol or less, preferably 9500 g / mol or more and 20000 g / mol or less, and more preferably 10000 g / mol or more and 20000 g / mol or less. When the weight average molecular weight of each of the first hard block and the second hard block satisfies the above numerical range, the physical crosslinking force between the binder and the negative electrode active material or the conductive material can be increased, so that a more stable three-dimensional network can be formed, and the electrode can be easily deformed when manufactured, thereby further improving the processability.
[0040] The first glass transition temperature and the second glass transition temperature corresponding to the first hard block and the second hard block, respectively, may be 50°C or more and 120°C or less, and the third glass transition temperature corresponding to the soft block may be -120°C or more and -50°C or less. Preferably, the first glass transition temperature and the second glass transition temperature may be 80°C or more and 120°C or less, and the third glass transition temperature may be -120°C or more and -80°C or less, and more preferably, the first glass transition temperature and the second glass transition temperature may be 80°C or more and 110°C or less, and the third glass transition temperature may be -110°C or more and -80°C or less. As described above, the first hard block, the second hard block and the soft block contained in the ternary block copolymer have glass transition temperatures within the above numerical range, so the negative electrode forming composition of the lithium secondary battery containing the binder containing the ternary block copolymer can be more reversibly molded, and the durability and flexibility of the electrode manufactured by the composition can be further improved, and its morphology can be more effectively maintained.
[0041] The soft block, the first hard block and the second hard block contained in the ternary block copolymer may not affect each other and show independent properties, so the soft block can provide flexibility to the negative electrode self-supporting film of the final lithium secondary battery, and the first hard block and the second hard block can each provide a strong binding force with the negative electrode active material to the negative electrode self-supporting film of the final lithium secondary battery. In addition, the soft block and the hard block have glass transition temperatures different from each other, so when the negative electrode self-supporting film is made (calendering, etc.) at a temperature equal to or higher than the glass transition temperature of the hard block, the ternary block copolymer is easy to shape, and is immediately exposed to the temperature corresponding to the glass transition temperature lower than the hard block and equal to or higher than the glass transition temperature of the soft block after film making, so that the ternary block copolymer has flexibility while maintaining high strength, and the negative electrode self-supporting film of the lithium secondary battery thus manufactured can be not easily broken due to external stimulation.
[0042] The ternary block copolymer is stable at a negative potential, so that the occurrence of side reactions is suppressed. Therefore, when the ternary block copolymer is used as a binder for a negative electrode of a lithium secondary battery, the life characteristics of the electrode can be improved.
[0043] The binder may be substantially spherical, and may be spherical or nearly spherical, and specifically, the average sphericity of the binder may be 0.7 or more and 1.0 or less, preferably 0.8 or more and 1.0 or less, and more preferably 0.9 or more and 1.0 or less. That is, before manufacturing the negative electrode self-supporting film, the particles of the binder in the negative electrode forming composition of the lithium secondary battery containing the binder may be substantially dispersed in the negative electrode forming composition while maintaining a spherical shape.
[0044] Among them, the sphericity of the adhesive is a value obtained as follows, that is, using an image of the adhesive particles observed by a scanning electron microscope (SEM), measuring the major and minor diameters of 10 randomly selected particles, and calculating the minor diameter / major diameter ratio of each particle. The value obtained by the average value of the minor diameter / major diameter ratio is that the closer the sphericity is to 1, the closer it can be judged to be to a sphere.
[0045] The negative electrode active material may include at least one selected from the group consisting of a carbon-based active material, a silicon-based active material, a metal-based active material capable of forming an alloy with lithium, and a lithium-containing active material.
[0046] The carbon-based active material may be, for example, graphite, hard carbon, soft carbon or graphene. The graphite may be artificial graphite, natural graphite, a mixture of artificial graphite and natural graphite, natural graphite coated with artificial graphite or a combination thereof.
[0047] The crystal structure of the carbon-based active material changes little during the insertion and extraction of lithium ions. Therefore, a continuous and repeated redox reaction can be carried out in the electrode, and thus a lithium secondary battery with high capacity and more excellent lifespan can be achieved.
[0048] The silicon-based active material can be, for example, Si, SiO m , Si-C composite, Si-Q alloy, or a combination thereof, where 0 < m ≤ 2, and Q is an alkali metal, alkaline earth metal, Group 13 to Group 16 element, transition metal, rare earth element, or a combination thereof, excluding Si in Q.
[0049] The metal-based active material capable of forming an alloy with lithium can be, for example, B, Al, Ga, In, Ge, Sn, Pb, P, As, Sb, Bi, Mg, Ca, Zn, Cd, Pd, Ag, Au, Pt, their alloys, or their oxides.
[0050] The lithium-containing active material can be, for example, lithium-containing titanium composite oxide (LTO).
[0051] The conductive material can include at least one selected from graphite, activated carbon, carbon black, acetylene black, Ketjen black, carbon nanotubes, graphene, and carbon fiber.
[0052] The film-forming process can be carried out by a dry method. That is, the composition for forming the negative electrode of the lithium secondary battery used in the film-forming process can substantially not contain a solvent. When the film-forming process is carried out by a wet method, due to the slurry in a liquid state, there are limitations in increasing the electrode loading amount, and there is a case where a network structure cannot be formed between the binder and the active material / conductive material. However, according to the film-forming process of the present invention, which is carried out by a dry method, a lithium secondary battery can be manufactured that has a high electrode loading amount for achieving a high energy density while more effectively forming a network structure between the binder and the active material.
[0053] The film-forming process can include calendering. That is, the composition for forming the negative electrode of the lithium secondary battery containing the negative electrode active material, conductive material, and binder can be extruded and calendered by passing between a pair of rollers to form a negative electrode active material layer. At this time, the diameter of the rollers can be, for example, 50 - 1000 mm, preferably 100 - 1000 mm, and more preferably 100 - 500 mm.
[0054] The calendering may be performed at a temperature equal to or higher than the first glass transition temperature and the second glass transition temperature corresponding to the first hard block and the second hard block, respectively. Specifically, the calendering may be performed at 50-140° C., preferably at 80-140° C., and more preferably at 80-130° C. Therefore, the moldability of the ternary block copolymer including the first hard block and the second hard block and the adhesive including the ternary block copolymer may be further improved.
[0055] By applying external forces such as shear force and tensile force through the rolling as described above, a self-supporting film for a negative electrode of a lithium secondary battery can be finally produced.
[0056] Specifically, the negative electrode active material layer manufactured by the dry method may be a free-standing negative electrode active material layer. The free-standing negative electrode active material layer refers to a negative electrode active material layer that is made into a thin film or film form that maintains a prescribed form without being supported by other substrates, etc. By manufacturing the free-standing negative electrode active material layer as described above, the subsequent lamination process can be smoothly carried out.
[0057] The average thickness of the self-supporting film obtained as described above may be 30 μm or more and 500 μm or less, preferably 50 μm or more and 300 μm or less, and more preferably 70 μm or more and 200 μm or less.
[0058] According to another embodiment of the present invention, a self-supporting film for a negative electrode of a lithium secondary battery is provided, wherein the self-supporting film for a negative electrode of a lithium secondary battery comprises a negative electrode active material layer, wherein the negative electrode active material layer comprises a plurality of domains of negative electrode active materials, a plurality of domains of conductive materials and a binder, wherein the binder comprises a ternary block copolymer, wherein the ternary block copolymer comprises: a soft block, wherein the soft block is derived from an aliphatic or alicyclic diene monomer and is in a rubber phase at room temperature; and a first hard block and a second hard block, wherein the first hard block and the second hard block are respectively connected to the two ends of the soft block, wherein the first hard block and the second hard block are derived from an ethylenically unsaturated monomer containing an aromatic ring and are in a glass phase at room temperature, and wherein the binder has a discontinuous columnar morphology connecting any one domain of active material or domain of conductive material with another domain of active material or domain of conductive material.
[0059] For the ternary block copolymer including the soft block, the first hard block and the second hard block, the same contents as explained above for the method of manufacturing a self-supporting film for a negative electrode of a lithium secondary battery can be applied.
[0060] The domain of any one of the active materials or the domain of the conductive material and the domain of another active material or the domain of the conductive material can be connected to each other by the discontinuous columnar (or linear) adhesive to form a three-dimensional network. That is, by connecting the outer surface of the domain of any one of the active materials or the conductive material with the surface of the domain of another active material or the conductive material with a discontinuous columnar (or linear) adhesive, a composite of a three-dimensional network structure of a network (active material or conductive material is located at the intersection, and a linear adhesive connects the active material and the conductive material) can be formed. The three-dimensional network as described above can be based on the strong π-π interaction between the first hard block and the second hard block contained in the ternary block copolymer and the negative active material or the conductive material.
[0061] Specifically, during the film forming process, in the initial stage, the binder containing the ternary block copolymer comes into contact with the negative electrode active material or the conductive material due to high external force (shear force or tensile force, etc.), and then in the later stage of the film forming process, as the external force decreases, the distance between the negative electrode active material or the conductive material increases, and the binder containing the ternary block copolymer in contact with the surface of the negative electrode active material or the conductive material undergoes flexibly deformation while maintaining its bonding, thereby having a discontinuous columnar or linear shape.
[0062] In addition, the ternary block copolymer can be subjected to pressure at the temperature of the film-making process to change into a columnar form to form a three-dimensional network. As described above, the domains of the active material or the domains of the conductive material are connected to the binder in the intermittent columnar form to form a three-dimensional network, so that the negative electrode of the lithium secondary battery with excellent tensile strength can be manufactured.
[0063] The average width of the adhesive perpendicular to the longitudinal direction thereof may be 0.2 μm to 2 μm, preferably 0.2 μm to 0.8 μm, and more preferably 0.3 μm to 0.7 μm.
[0064] The average width perpendicular to the length direction of the columnar adhesive contained in the self-supporting film is a value obtained by measuring the width perpendicular to the length direction at both ends and the center of 5 randomly selected columnar adhesives along the length direction using an image of the adhesive particles observed by a scanning electron microscope (SEM), and obtaining the value from the average of these measured values.
[0065] The average thickness of the self-supporting film may be 30 μm or more and 500 μm or less, preferably 50 μm or more and 300 μm or less, and more preferably 70 μm or more and 200 μm or less.
[0066] The tensile strength of the self-supporting film may be greater than 0.5 MPa, preferably greater than 0.7 MPa, and more preferably greater than 1.0 MPa.
[0067] According to another embodiment of the present invention, there is provided a negative electrode for a lithium secondary battery, the negative electrode for a lithium secondary battery comprising: a current collector; and a self-supporting film for the negative electrode of the lithium secondary battery disposed on the current collector.
[0068] When the self-supporting film for the negative electrode of the lithium secondary battery is formed by the film-making process, the self-supporting film for the negative electrode of the lithium secondary battery can be arranged on the current collector and laminated. The lamination can be performed by a lamination roller, and at this time, the lamination roller can be maintained at a temperature of 80-200° C. Through the lamination process as described above, the self-supporting film for the negative electrode of the lithium secondary battery and the current collector can be bonded.
[0069] The current collector is not particularly limited as long as it does not cause chemical changes in the battery and has high conductivity. For example, stainless steel, aluminum, nickel, titanium, calcined carbon, copper or alloys thereof, or a material obtained by surface-treating the surface of stainless steel with carbon, nickel, titanium, silver, etc., can be used.
[0070] According to another embodiment of the present invention, there is provided a lithium secondary battery, the lithium secondary battery comprising: a negative electrode for the lithium secondary battery; a positive electrode for the lithium secondary battery; and an electrolyte.
[0071] The positive electrode for the lithium secondary battery may include one or more positive electrode active materials selected from lithium, nickel, cobalt, manganese, iron, tin, silicon, aluminum and mixtures thereof. As a specific example, LiCoO 2 、LiMnO 2 、LiFeO 2 、Li(Ni 0.6 Mn 0.2 Co 0.2 ) 2 、Li(Ni 0.7 Mn 0.15 Co 0.15 ) 2 、Li(Ni 0.8 Mn 0.1 Co 0.1 ) 2 、Li(Ni 0.9 Mn 0.05 Co 0.05 ) 2 、LiNi 0.6 Co 0.2 Al 0.2 O 2、 LiNi 0.7 Co0.2 Al 0.1 O 2、 LiNi 0.8 Co 0.15 Al 0.05 O 2 、LiNi 0.85 Co 0.1 Al 0.05 O 2 、LiNi 0.88 Co 0.1 Al 0.02 O 2 、LiMn 2 O 4 、LiFePO 4 Positive electrode active materials.
[0072] The electrolyte may be a liquid electrolyte or a solid electrolyte.
[0073] When the electrolyte is a liquid electrolyte, the electrolyte may include a lithium salt and a non-aqueous organic solvent.
[0074] The lithium salt may be used without limitation as long as it is generally used as an electrolyte for lithium secondary batteries. For example, the lithium salt may include a selected from LiPF 6 , LiBF 4 、LiSbF 6 、LiAsF 6 、LiN(C 2 F 5 SO 2 ) 2 、LiN(CF 3 SO 2 ) 2 CF 3 SO 3 Li、LiC(CF 3 SO 2 ) 3 ,LiC 4 BO 8 , LiTFSI, LiFSI and LiClO 4 More than one compound in .
[0075] The non-aqueous organic solvent may include organic solvents of the type that can be used as non-aqueous electrolytes when manufacturing conventional lithium secondary batteries, and their contents may be appropriately changed within a generally usable range.
[0076] Specifically, the nonaqueous organic solvent may include conventional organic solvents that can be used as nonaqueous organic solvents for lithium secondary batteries, such as cyclic carbonate solvents, linear carbonate solvents, ester solvents or ketone solvents, and they may be used alone or in combination of two or more.
[0077] The cyclic carbonate solvent may include at least one selected from the group consisting of ethylene carbonate (EC), vinylene carbonate (VC), fluoroethylene carbonate (FEC), propylene carbonate (PC), and butylene carbonate (BC).
[0078] The linear carbonate solvent may include one or more selected from dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate (DPC), ethyl methyl carbonate (EMC), methyl propyl carbonate (MPC), and ethyl propyl carbonate (EPC).
[0079] The ester solvent may include one or more selected from methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, γ-butyrolactone, γ-valerolactone, γ-caprolactone, δ-valerolactone, and ε-caprolactone.
[0080] As the ketone solvent, polymethyl vinyl ketone or the like can be used.
[0081] When the electrolyte is a liquid electrolyte, the lithium secondary battery may further include a separator.
[0082] The separator can use a commonly used porous polymer film, for example, a porous polymer film prepared from polyolefin-based polymers such as ethylene homopolymers, propylene homopolymers, ethylene / butene copolymers, ethylene / hexene copolymers, and ethylene / methacrylate copolymers can be used alone or in layers, or a conventional porous non-woven fabric can be used, for example, a non-woven fabric formed of high-melting-point glass fibers, polyethylene terephthalate fibers, etc. can be used, but is not limited thereto. In addition, in order to ensure heat resistance or mechanical strength, a coated separator containing a ceramic component or a polymer substance can also be used, and can be selectively used in a single-layer or multi-layer structure.
[0083] At this time, the pore diameter of the porous membrane may generally be 0.01-50 μm, the porosity may be 5-95%, and the thickness of the porous membrane may generally be in the range of 5-300 μm.
[0084] In addition, when the electrolyte is a solid electrolyte, the electrolyte may be a polymer-based solid electrolyte, an oxide-based solid electrolyte, a sulfide-based solid electrolyte, or a mixture thereof.
[0085] The polymer-based solid electrolyte may include, for example, polyether-based polymers, polycarbonate-based polymers, acrylate-based polymers, polysiloxane-based polymers, phosphazene-based polymers, polyethylene derivatives, alkylene oxide derivatives such as polyethylene oxide, phosphate polymers, polyagitation lysine, polyester sulfide, polyvinyl alcohol, polyvinylidene fluoride and its derivatives, polymers containing ion dissociation groups, etc. In addition, the polymer electrolyte may include, as polymer resins, branched copolymers, comb-like polymer resins, and cross-linked polymer resins, in which the main chain of polyethylene oxide (PEO) is copolymerized with amorphous polymers such as PMMA, polycarbonate, polysiloxane, and / or phosphazene as comonomers, and may include more than one of them.
[0086] The oxide-based solid electrolyte may include, for example, LLZO-based compounds, Li 3x La 2 / 3-x TiO 3 LLTO-based compounds, Li 14 Zn(GeO 4 ) 4 Lithium superion conductor (LISICON) based compounds, Li 1.3 Al 0.3 Ti 1.7 (PO 4 ) 3 LATP-based compounds, (Li 1+x Ge 2-x Al x (PO 4 ) 3 ) and the like, and are not particularly limited thereto.
[0087] The sulfide-based solid electrolyte may include Li 6 PS 5 Cl, Li 2 SP 2 S 5 , Li 2 S-LiI-P 2 S 5 , Li 2 S-LiI-Li 2 OP 2 S 5 , Li 2 S-LiBr-P 2 S 5 , Li 2 S-Li2 OP 2 S 5 , Li 2 SLi 3 PO 4 -P 2 S 5 , Li 2 SP 2 S 5 -P 2 O 5 , Li 2 SP 2 S 5 -SiS 2 , Li 2 SP 2 S 5 -SnS、Li 2 SP 2 S 5 -Al 2 S 3 , Li 2 S-GeS 2 or Li 2 S-GeS 2 -ZnS, but is not particularly limited thereto.
[0088] Hereinafter, the present invention will be described in more detail by way of examples. However, these examples are only used for understanding the present invention, and the scope of the present invention is not limited to these examples in any sense.
[0089] <Example 1> Production of Self-Supporting Film for Negative Electrode 1
[0090] First, graphite as a negative electrode active material, carbon black as a conductive material, and SBS ternary block copolymer (glass transition temperature of polystyrene block: 100°C, glass transition temperature of polybutadiene block: -100°C) as a binder were mixed in a mass ratio of 96:1:3 without a solvent. The mixed powder was rolled using a double roll press heated to a temperature of 120°C to produce a self-supporting film.
[0091] <Comparative Example 1> Production of Self-Supporting Film for Negative Electrode 2
[0092] A negative electrode self-supporting film was produced by the same method as in Example 1 except that PTFE was used as the binder instead of SBS and the mixed powder was rolled using a twin roll press heated to 80°C.
[0093] <Comparative Example 2> Preparation of SBR Negative Electrode Coating
[0094] 5.8 g of carboxymethyl cellulose (CMC) was stirred at 500 rpm for 12 hours to dissolve in 255.5 g of distilled water, and then 17.5 g of an aqueous solution of 40 wt % styrene-butadiene rubber (SBR) was added and further stirred for 6 hours to completely dissolve, thereby synthesizing a CMC / SBR (1 / 1.2) adhesive dispersion in which 5 parts by weight of CMC / SBR was dissolved relative to 100 parts by weight of the solution.
[0095] Then, graphite as a negative electrode active material, carbon black as a conductive material, and the CMC / SBR binder dispersion were mixed at a mass ratio of 96.8:1:2.2, and the mixed slurry was coated on copper with a thickness of about 100 μm and dried at 120° C.
[0096] <Experimental Example 1> Observation of SEM images of negative electrode self-supporting films
[0097] The SEM image of the negative electrode self-supporting film manufactured according to Example 1 is shown in FIG. Figure 3a to Figure 3c In addition, in order to compare the morphological changes of the binder after the film-forming process, SEM images of the initial SBS binder and the mixed powder of graphite, conductive material and binder before the film-forming process were taken and are shown in Figure 3e and Figure 3f In addition, the SEM images of the negative electrode self-supporting films manufactured according to Comparative Examples 1 and 2 are shown in Figure 3g , Figure 3i and Figure 3j middle.
[0098] See also Figure 3a It was confirmed that the thickness of the negative electrode self-supporting film formed by the film forming process was about 105 μm.
[0099] In addition, according to Figure 3b and Figure 3c It can be confirmed that the columnar SBS binder after the film forming process forms a network structure connecting the negative electrode active materials, the conductive materials, or the negative electrode active materials and the conductive materials, and has a columnar shape with an average width of about 0.4-0.5 μm perpendicular to its length direction.
[0100] Figure 3d Schematically shows a columnar SBS binder connecting negative electrode active materials in the network structure of the negative electrode self-supporting film manufactured according to Example 1. That is, it can be seen that the intermittent SBS binder showing a columnar morphology is in point contact with the outer surface of each active material domain or conductive material domain to connect them.
[0101] in addition, Figure 3e The SEM image of the SBS powder before preparing the negative electrode forming composition is shown in FIG. The image shows an almost spherical shape, and Figure 3f This is a SEM image of the negative electrode forming composition (powder mixed with negative electrode active material, conductive material and SBS binder before the film forming process). It can be confirmed that the SBS maintains a nearly spherical shape (average diameter (D 50 ): 8 μm, average sphericity: 0.95) and dispersed.
[0102] according to Figure 3g It can be confirmed that, unlike the case of Example 1, in the case of the PTFE binder, a three-dimensional network having a structure in which the binder connects the active material or the conductive material in a discontinuous columnar morphology is not formed.
[0103] Figure 3h The network structure in the self-supporting film for the negative electrode according to Comparative Example 1 is schematically shown. In the case of Comparative Example 1, the binder and the negative electrode active material are not connected as shown in Example 1, but the PTFE binders are connected to form a network structure, and the negative electrode active materials are randomly overlapped and located on the network structure instead of point contact (however, the portion shown as a blurred line partially covered by the active material particles corresponds to the network structure of the PTFE binder). There is a difference in this respect.
[0104] See also Figure 3i and Figure 3j It can be confirmed that when the wet electrode is produced using the SBR binder, a three-dimensional network formed by the binder having a columnar morphology is not observed.
[0105] <Experimental Example 2> Measurement of tensile strength of self-supporting film for negative electrode
[0106] In order to evaluate the tensile strength of the negative electrode self-supporting films manufactured according to Example 1 and Comparative Example 1, each supporting film was prepared by punching out into a width of 2 cm and a length of 6 cm, and then the tensile strength was measured at a speed of 5 mm / min using a UTM device.
[0107] The tensile strength of the negative electrode self-supporting film according to Example 1 was 1.06 MPa, and the tensile strength of the negative electrode self-supporting film according to Comparative Example 1 was 0.253 MPa. It was confirmed that the tensile strength of the negative electrode self-supporting film of Example 1 using SBS as a binder was significantly superior.
[0108] This is presumably because the SBS binder forms a three-dimensional network connecting active materials, conductive materials, or active materials and conductive materials, thereby forming a strong adhesive force.
[0109] <Example 2> Production of lithium secondary battery 1
[0110] The self-supporting film for a negative electrode according to Example 1 was disposed on one side of the copper foil coated with the undercoat layer, and laminated by a laminating roll maintained at 120° C. to manufacture a negative electrode of a lithium secondary battery.
[0111] A coin-type half-cell was fabricated using the negative electrode, lithium metal as a positive electrode, and an electrolyte, wherein the electrolyte contained 1 M LiPF in a solvent in which EC:EMC:DEC was mixed at a volume ratio of 25:45:30. 6 , 2 wt% vinylene carbonate (VC) and 1 wt% LiPO 2 F 2 of electrolyte.
[0112] <Comparative Example 3> Production of lithium secondary battery 2
[0113] A coin-type half cell was manufactured by the same method as in Example 2, except that the self-supporting film for a negative electrode according to Comparative Example 1 was used instead of the self-supporting film for a negative electrode according to Example 1.
[0114] <Experimental Example 3> Performance evaluation of lithium secondary batteries
[0115] For the lithium secondary batteries according to Example 2 and Comparative Example 3, 1 cycle was performed at a 0.1 C rate, and the charge capacity and discharge capacity were measured and shown in Table 1 below.
[0116] It was confirmed that in the case of the lithium secondary battery according to Example 2, i.e., the lithium secondary battery using the negative electrode self-supporting film according to Example 1, a more excellent charge and discharge efficiency was shown. Specifically, since the PTFE binder was used in the lithium secondary battery according to Comparative Example 3, a relatively large amount of lithium was consumed due to side reactions, so it can be seen that the charging capacity showed a higher value compared with the lithium secondary battery according to Example 2, and the overall efficiency was further reduced. On the other hand, it is speculated that since the SBS binder was used in the lithium secondary battery according to Example 2, the occurrence of side reactions was suppressed, and thus excellent efficiency was shown.
[0117] This is because PTFE has low stability at negative potentials due to its low LUMO level, so decomposition and side reactions occur, while the SBS binder has excellent stability at negative potentials due to its appropriate energy level.
[0118] [Table 1] <![CDATA[Negative electrode load (mg / cm 2 )]]> Charging capacity (mAh / g) Discharge capacity (mAh / g) efficiency(%) Example 2 26.2 387 346 89 Comparative Example 3 23.9 417 341 82
Claims
1. A method for manufacturing a self-supporting film for a negative electrode of a lithium secondary battery, the method comprising the step of forming a negative electrode active material layer by a film-making process using a composition for forming a negative electrode of a lithium secondary battery comprising a negative electrode active material, a conductive material and a binder, in, The adhesive comprises a ternary block copolymer, wherein the ternary block copolymer comprises: a soft block, wherein the soft block is derived from an aliphatic or alicyclic diene monomer and is in a rubber phase at room temperature; and a first hard block and a second hard block, wherein the first hard block and the second hard block are respectively connected to two ends of the soft block, wherein the first hard block and the second hard block are derived from an ethylenically unsaturated monomer containing an aromatic ring and are in a glass phase at room temperature. The adhesive comprises an average diameter D 50 The particles are 1 μm or more and 50 μm or less.
2. The method for producing a self-supporting film for a negative electrode of a lithium secondary battery according to claim 1, wherein: The binder is spherical, and its average sphericity is 0.8 or more and 1.0 or less.
3. The method for producing a self-supporting film for a negative electrode of a lithium secondary battery according to claim 1, wherein: The first glass transition temperature and the second glass transition temperature corresponding to the first hard block and the second hard block, respectively, are 50° C. or more and 120° C. or less, and the third glass transition temperature corresponding to the soft block is -120° C. or more and -50° C. or less.
4. The method for producing a self-supporting film for a negative electrode of a lithium secondary battery according to claim 1, wherein: The soft block is derived from an aliphatic diene-based monomer including at least one selected from a butadiene-based monomer, a pentadiene-based monomer, and a hexadiene-based monomer.
5. The method for producing a self-supporting film for a negative electrode of a lithium secondary battery according to claim 1, wherein: The first hard block and the second hard block are each independently derived from an aromatic ring-containing ethylenically unsaturated monomer including at least one of a styrene-based monomer and an aromatic (meth)acrylic-based monomer.
6. The method for producing a self-supporting film for a negative electrode of a lithium secondary battery according to claim 1, wherein: The negative electrode active material includes at least one selected from a carbon-based active material, a silicon-based active material, a metal-based active material capable of forming an alloy with lithium, and a lithium-containing active material.
7. The method for producing a self-supporting film for a negative electrode of a lithium secondary battery according to claim 1, wherein: The conductive material comprises at least one selected from graphite, activated carbon, carbon black, acetylene black, Ketjen black, carbon nanotubes, graphene and carbon fiber.
8. The method for producing a self-supporting film for a negative electrode of a lithium secondary battery according to claim 1, wherein: The film-making process is carried out by a dry method.
9. The method for producing a self-supporting film for a negative electrode of a lithium secondary battery according to claim 8, wherein: The film-making process includes calendaring at a temperature equal to or higher than a first glass transition temperature and a second glass transition temperature corresponding to the first hard block and the second hard block, respectively.
10. A self-supporting film for a negative electrode of a lithium secondary battery, the self-supporting film for a negative electrode of a lithium secondary battery comprising a negative electrode active material layer, the negative electrode active material layer comprising a plurality of domains of negative electrode active materials, a plurality of domains of conductive materials and a binder, in, The adhesive comprises a ternary block copolymer, wherein the ternary block copolymer comprises: a soft block, wherein the soft block is derived from an aliphatic or alicyclic diene monomer and is in a rubber phase at room temperature; and a first hard block and a second hard block, wherein the first hard block and the second hard block are respectively connected to two ends of the soft block, wherein the first hard block and the second hard block are derived from an ethylenically unsaturated monomer containing an aromatic ring and are in a glass phase at room temperature. The binder has a discontinuous columnar morphology that connects one domain of an active material or a domain of a conductive material with another domain of an active material or a domain of a conductive material.
11. The self-supporting film for a negative electrode of a lithium secondary battery according to claim 10, wherein: The domains of the active material or the conductive material and the binder in the form of discontinuous columns are connected to each other to form a three-dimensional network.
12. The self-supporting film for negative electrode of a lithium secondary battery according to claim 10, wherein: The adhesive has an average width perpendicular to the longitudinal direction thereof of 0.2 μm or more and 2 μm or less.
13. The self-supporting film for negative electrode of a lithium secondary battery according to claim 10, wherein: The first glass transition temperature and the second glass transition temperature corresponding to the first hard block and the second hard block, respectively, are 50° C. or more and 120° C. or less, and the third glass transition temperature corresponding to the soft block is -120° C. or more and -50° C. or less.
14. The self-supporting film for a negative electrode of a lithium secondary battery according to claim 10, wherein: The soft block is derived from an aliphatic diene-based monomer including at least one selected from a butadiene-based monomer, a pentadiene-based monomer, and a hexadiene-based monomer.
15. The self-supporting film for negative electrode of a lithium secondary battery according to claim 10, wherein: The first hard block and the second hard block are each independently derived from an aromatic ring-containing ethylenically unsaturated monomer including at least one of a styrene-based monomer and an aromatic (meth)acrylic-based monomer.
16. The self-supporting film for negative electrode of a lithium secondary battery according to claim 10, wherein: The self-supporting film has an average thickness of 30 μm or more and 500 μm or less.
17. The self-supporting film for negative electrode of a lithium secondary battery according to claim 10, wherein: The self-supporting film has a tensile strength of 0.5 MPa or more.
18. A negative electrode for a lithium secondary battery, comprising: current collector; as well as The self-supporting film for a negative electrode of a lithium secondary battery according to any one of claims 10 to 17 is provided on the current collector.
19. A lithium secondary battery comprising: The negative electrode for a lithium secondary battery according to claim 18; Positive electrode for lithium secondary battery; as well as Electrolytes.